INCREATION STKIP ; DIGITAL MEDIA LEARNING BASED ON LOCAL WISDOM FOR STKIP PGRI SUMENEP STUDENTS - Basri, Hasan (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2022)
The College of Teacher Training and Education, called STKIP, is a space and forum for students who focus on the world of education. STKIP is considered the only miniature university which focuses on education. The INCREATION of STKIP, the Digital Media Innovation Based on Local Wisdom to Create Collaborative STKIP College Students, is an idea coming from the phenomenon of regional cultures that are rapidly being eroded. The importance of increasing the digital literacy among students needs all STKIP students solidarity in realizing a good quality of education for a superior and resilient Indonesia. The method applied in this paper is a qualitative descriptive approach that also observes a socio-culture through the developmental research methodology to investigate the existence of sequence and pattern of growth or changes in the area of Sumenep Regency related to its local cultures using the domain analysis. As a result, the existence of INCREATION media is expected to influence all STKIP students to collaborate in creating humanization in the world of education through the Local Cultures.